Botanical extracts in combination improve autosomal recessive woolly hair/hypotrichosis caused by LIPH mutations. (22nd March 2022) - Qu, Baoquan; Meng, Shengnan; Yang, Chaowei; Lv, Shuying; Lin, Wenjun; Yang, Dingquan
ABSTRACT: Background: Mutation in the lipase H (LIPH) gene is a main reason for autosomal recessive woolly hair (ARWH)/hypotrichosis. Although some studies reported that topical minoxidil could improve ARWH, an effective treatment method for this disease is still lacking. Aim: We attempt to explore potential treatment options for ARWH. Materials & Methods: A female 6‐year‐old child was diagnosed with ARWH/hypotrichosis caused by LIPH mutations. And she was treated with combined treatment of botanical extracts. Results: After 6 months of treatment, the patient's hair grew remarkably. After 4 years of treatment, the patient's hair remained dense. Discussion: After the combination treatment, the patient saw a favorable clinical effect. However, the specific mechanisms of action for botanical extracts require further validation. In addition, some regenerative strategies may be considered as potential treatment options for ARWH. We should actively attempt treatment for ARWH patients and encourage prenatal diagnosis due to the great impact of hair loss. Conclusion: The combined therapy of botanical extracts may improve ARWH long‐term with a sustainable therapeutic effect.